Turkey's role in natural gas: Becoming a transit country? - Istemi Berk; Simon Schulte (Institute of Energy Economics at the University of Cologne (EWI), 2017)
This paper analyses the possible future role that Turkey can play in European natural gas markets. We employ a global gas market simulation model, COLUMBUS, to assess the outcomes of different scenarios concerning natural gas supply routes to Europe through Turkey up to 2030. The results imply simply that under current conditions, i.e., a more competitive environment in European gas markets leading to low gas prices, Turkey's role would be of only minor importance. In accordance with various scenarios presented in this study, Turkey's role is seen at its most important when European demand increases and Russia exerts power in the European markets.
Keywords: C68; L13; Q31; 330; COLUMBUS; European gas supply; Turkey; scenario analyses